(untitled) (Fiep Bulletin - online, 2014)
This article aims to show the apparatus that supports the groundwork and support teams representing the Brazilian volleyball can develop to the full. It was highlighted aspects of the Brazilian Confederation of Volleyball (CBV), The Development Centre Volleyball - Saquarema (Aryzão); Institute VivaVôlei; University Official Brazilian Volleyball; Superliga; Superliga B; registration coach and qualification; Preparer Registration physical and anthropometric profile of Brazilian teams. We conclude that although we have in Brazil a large population density and various imbalances of social and economic order we note that in terms of volleyball income country manages investments through short, medium and long term to keep as a reference work in the scenario world, always occupying the best places in the ranks and revealing new talents every day.